Functional domains of the mouse β3-adrenoceptor associated with differential G-protein coupling. (25th October 2007) - Sato, M.; Hutchinson, D.S.; Evans, B.A.; Summers, R.J.
Abstract : Localization of G-protein-coupled receptors within membrane microdomains is associated with differential signalling pathway activation. We have shown that two mouse β3 -AR (β3 -adrenoceptor) isoforms encoded by alternatively spliced mRNAs differ in their signalling properties; the β3a -AR couples only with Gs, whereas the β3b -AR couples with both Gs and Gi . Our previous studies indicated that the β3a -AR is restrained from coupling with Gi due to the interaction of residues in the C-terminus with other protein(s). We have investigated the hypothesis that the β3a -AR interacts with caveolin. Disruption of caveolae in CHO (Chinese-hamster ovary)-K1 cells expressing wild-type β3a -ARs with filipin III, or mutation of a putative caveolin-binding site in the β3a -AR, causes cAMP accumulation to become PTX (pertussis toxin)-sensitive. Likewise, filipin treatment of mouse brown adipocytes that express endogenous β3a -ARs produces a substantial reduction in agonist-stimulated cAMP production that is rescued by pre-treatment with PTX. These studies suggest that β3a -ARs may be restricted to caveolae and that localization of the receptor may play a specific role in G-protein-mediated signalling.